Business ethics and corporate governance - Ghosh-B (McGraw Hill, 2012)
Business Ethics and Corporate Governance is a research based textbook with many meta-theoretic ideas, analyticalintrospections and didactic models expressed by the author. Comprehensively written, it encompasses latestdevelopments, contemporary issues and polemics. It also develops critical thinking and resolve ethical issues that arise in all the functional areas of businesses. The book provides theories and empirics on every topical issue with illustrations, examples and cases which would help the students in effective decision making as practicing managers.